Developments in drug design strategies for bromodomain protein inhibitors to target Plasmodium falciparum parasites. (2nd April 2020) - Nguyen, Hanh H. T.; Yeoh, Lee M.; Chisholm, Scott A.; Duffy, Michael F.
ABSTRACT: Introduction : Bromodomains (BRDs) bind to acetylated lysine residues, often on histones. The BRD proteins can contribute to gene regulation either directly through enzymatic activity or indirectly through recruitment of chromatin-modifying complexes or transcription factors. There is no evidence of direct orthologues of the Plasmodium falciparum BRD proteins (PfBDPs) outside the apicomplexans. PfBDPs are expressed during the parasite's life cycle in both the human host's blood and in the mosquito. PfBDPs could also prove to be promising targets for novel antimalarials, which are urgently required to address increasing drug resistance. Areas covered : This review discusses recent studies of the biology of PfBDPs, current target-based strategies for PfBDP inhibitor discovery, and different approaches to the important step of validating the specificity of hit compounds for PfBDPs. Expert opinion : The novelty of Plasmodium BRDs suggests that they could be targeted by selective compounds. Chemical series that showed promise in screens against human BRDs could be leveraged to create targeted compound libraries, as could hits from P. falciparum phenotypic screens. These targeted libraries and hits could be screened in target-based strategies aimed at discovery and optimization of novel inhibitors of PfBDPs. A key task for the field is to generate parasite assays to validate the hit compounds' specificity for PfBDPs.